Christian martyrdom and political violence: a comparative theology with Judaism and Islam - Rosario Rodríguez, Rubén (Cambridge University Press, 2017)
In recent years, martyrdom and political violence have been conflated in the public imagination. Rubén Rosario Rodríguez argues that martyr narratives deserve consideration as resources for resisting political violence in contemporary theological reflection. Underlying the three Abrahamic monotheistic traditions is a shared belief that God requires liberation for the oppressed, justice for the victims and, most demanding of all, love for the political enemy. Christian, Jewish and Muslim martyr narratives that condone political violence - whether terrorist or state-sponsored - are examined alongside each religion's canon, in order to evaluate how central or marginalized these discourses are within their respective traditions. Primarily a work of Christian theology in conversation with Judaism and Islam, this book aims to model religious pluralism and cooperation by retrieving distinctly Christian sources that nurture tolerance and facilitate coexistence, while respecting religious difference.